IMF Staff papers : Volume 15 No. 3. - International Monetary Fund. Research Dept. (Washington, D.C. : International Monetary Fund, 1968)
This paper focuses on problems of economic policy in terms of targets and instruments. Both the fixed-targets approach and the welfare-economics approach tend to favor a multiplication of policy instruments, the former so as to increase the number of targets that can be attained and the latter so as to permit all objectives to be more closely approximated. It is necessary that policies be centrally coordinated, and in each country, there is a limit to the number of policies that can be successfully coordinated by the political and administrative machine. For this reason, the costs of applying any given policy instrument will depend not only on the degree of its use but also on the number and nature of the instruments already in use. The existence of both kinds of cost, and particularly the latter, will set a limit on the number of policy instruments that can appropriately be brought into operation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet